MICROARRAY GENE EXPRESSION MIAME-PLANT SUPPORTIVE TAB DELIMITED DATA FORMAT: MAGE-TAB-PLANT - S. U. Rehman; Atif A. Mirza; K. Masood; B. Rashid; T. Husnain (Journal of Animal and Plant Sciences, 2014)
The goal of Minimum Information about a Microarray Experiment (MIAME) is to outline the minimum information that can clearly state the microarray based gene expression experiment in such a way that the details of experiment design, description and sample annotation can help to check and reproduce the results in some other laboratory. MIAME/plant complements the MIAME standard with guideline for experiment design, description and sample preparation protocols using controlled vocabularies. MAGE-TAB-Plant format has been structured on the similar lines as MAGE-TAB format.  It explains the main chain of all events in a typical Microarray based experiment such as steps involved in preparation and handling of samples, labelling and hybridization protocols, scanning of images, normalization of raw data and analysis of images. The physical entities in this chain are Biosource, Sample, Extract, labelled Extract, hybridization, scan image, raw, normalized and combined data matrix. It is hoped that little more effort may result in better precisely replicated, analyzed, and better interpreted reproducible plant based microarray experiments. Data mining capabilities of data submitted using MAGE-TAB-Plant format may generate breakthroughs in research and the use of controlled vocabularies may encourage efficient sharing and annotation of the experiment data.
Keywords: Microarray; Data format; Tab delimited; MIAME